2008
DOI: 10.1007/s12094-008-0196-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification: an effective new approach to oocyte banking and preserving fertility in cancer patients

Abstract: Oocyte cryo-banking by means of the Cryotop vitrification method represents a viable option for healthy women, producing excellent survival rates and a clinical outcome similar to that obtained with fresh oocytes. This approach could potentially be used in cancer patients who want to safeguard their fertility. Cancer patients could potentially benefit from this approach by storing their oocytes before the onset of the oncological therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
1
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(69 citation statements)
references
References 45 publications
1
63
1
4
Order By: Relevance
“…While embryo banking is currently considered the only standard (non-experimental) procedure, improved success with oocyte banking and ovarian tissue banking offer single females the possibility of having biological children with a future partner. Live birth rates after oocyte banking have been reported to range between 2% and 5% per oocyte banked, and over 1,000 births have been reported to date [14,[21][22][23]. Autologous transplantation of previously frozen and thawed ovarian cortical tissue has resulted in 13 live births to date [24], including a live birth in a patient with sickle cell disease treated with HCT [25].…”
Section: Discussionmentioning
confidence: 99%
“…While embryo banking is currently considered the only standard (non-experimental) procedure, improved success with oocyte banking and ovarian tissue banking offer single females the possibility of having biological children with a future partner. Live birth rates after oocyte banking have been reported to range between 2% and 5% per oocyte banked, and over 1,000 births have been reported to date [14,[21][22][23]. Autologous transplantation of previously frozen and thawed ovarian cortical tissue has resulted in 13 live births to date [24], including a live birth in a patient with sickle cell disease treated with HCT [25].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, multiple clinics have reported IVF successes after transfer of embryos derived from frozen/ thawed oocytes [5,[14][15][16][17][18][19][20]. The authors have recently reported that oocytes from young fertile women retain their reproductive potential after 6 months of vitrification cryopreservation [20] and the pregnancy and implantation rates are comparable to that of frozen embryos.…”
Section: Conclusion(s)mentioning
confidence: 99%
“…The recent increased interest in vitrification has resulted in improved efficiency and pregnancy outcomes [2][3][4][5][6][7][8][9][10][11][12][13]. Being able to protect and prolong the reproductive capacity by way of oocyte cryopreservation potentially opens the door for many thousands of women who are at a risk of losing ovarian function from radiation, chemotherapy and surgery.Over the last decade, multiple clinics have reported IVF successes after transfer of embryos derived from frozen/ thawed oocytes [5,[14][15][16][17][18][19][20]. The authors have recently reported that oocytes from young fertile women retain their reproductive potential after 6 months of vitrification cryopreservation [20] and the pregnancy and implantation rates are comparable to that of frozen embryos.…”
mentioning
confidence: 99%
“…Advances in reproductive techniques have provided many fertility preservation options [4]. However, initial trials on oocyte cryopreservation were limited by spindle misalignment and errors in the chromosomal arrangement due to ice formation inside the oocytes during the process [5].…”
Section: Introductionmentioning
confidence: 99%